THE POTENTIAL OF HERBAL PLANT EXTRACTS AS A COMPLEMENTARY THERAPY IN DIABETES MELLITUS: A LITERATURE REVIEW - Prameswari, Shafira Audy; Afifah, Afifah; Pratiwi, Meidy; Rahmania, Firda; Fatah, Muhammad Riski; Ningsih, Elisa Fitria; Maulana, Krisna; Khaerunnisa, Ghina Eka Nur (Medical and Health Journal, 2024)
Diabetes mellitus (DM) is still a serious health problem that needs attention in Indonesia. Management of this disease can be done with conventional therapy that has been commonly practiced. However, advances in DM treatment approaches have side effects such as hypoglycemic coma, liver disorders, and kidney disorders. The way to overcome this is by combining medicinal plants and conventional therapy. However, the lack of scientific research or testing that illustrates the effectiveness of herbal plants is still a problem in the use of herbal plants. This literature study provides a scientific overview of the effectiveness of herbal extracts as complementary therapy for DM. The literature search was conducted through online data sites PubMed, Science Direct, Research Gate, and Google Scholar using the keywords (Antidiabetic) AND (Herbs) from 2013 to 2023. From the search results, 13 articles were obtained that met the eligibility criteria. Based on tests conducted in each article obtained, all herbal extracts studied have anti-diabetic properties that can reduce blood glucose levels depending on the dose given. This finding suggests that herbal extracts can be utilized as complementary therapy for people suffering from DM.